Trend Analysis of Climatic Variables at Mulde Location of Maharashtra State - Jagtap, D. N; Ingle, P. M; Mule, R. S; Bodake, P. S; Burondkar, M. M (International Journal of Sustainable Agricultural Research, 2020)
The present study comprises the seasonal & annual trends of different climatic variables for Mulde location of Maharashtra state. The trend analysis for different climatic variables such as maximum temperature (TMax), minimum temperature (TMin), rainfall (RF), morning relative humidity (RH I), afternoon relative humidity (RH II), evaporation (EVP), wind speed (WS) and sunshine hours (BSS) was carried out for 25 years from 1991-2015. The trend of TMax was tested and indicated that the trend was significantly increasing except southwest monsoon while in case of TMin trend was non significantly increasing during different periods. In case of rainfall trend was increasing during annual, winter and summer but statistically non-significant at 95 % level of significance and during southwest monsoon and northeast monsoon decreasing trend but statistically non-significant at 95 % level of significance. The trend analysis for RH I indicated that during annual, summer and northeast season the trend was significantly increasing at 95 % level of significance and while RH II, linear regression analysis indicated for all periods the trend was significantly increasing. In case of evaporation, analysis indicated that trends of all periods increasing and statistically significant at 95 % level of significance except summer and northeast monsoon while for BSS, indicated that trend was decreasing and statistically significant at 95 % level of significance except southwest monsoon. In case of WS, analysis showed that trend was significantly decreasing for all periods at 95 % level of significance.